Nanotwin-governed toughening mechanism in hierarchically structured biological materials - Yoon Ah Shin (Nature Portfolio, 2016)
As a natural biocomposite, Strombus gigas, commonly known as the giant pink queen conch shell, exhibits outstanding mechanical properties such as fracture toughness. Here, the authors show that these properties can be partially attributed to nanoscale twin boundaries in the basic building block of the shell.